2015
DOI: 10.1002/psp4.12007
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model Characterizing 24‐Hour Variation in the Pharmacokinetics of Oral and Intravenous Midazolam in Healthy Volunteers

Abstract: Daily rhythms in physiology may affect the pharmacokinetics of a drug. The aim of this study was to evaluate 24-hour variation in the pharmacokinetics of the CYP3A substrate midazolam. Oral (2 mg) and intravenous (1 mg) midazolam was administered at six timepoints throughout the 24-hour period in 12 healthy volunteers. Oral bioavailability (population mean value [RSE%] of 0.28 (7.1%)) showed 24-hour variation that was best parameterized as a cosine function with an amplitude of 0.04 (17.3%) and a peak at 12:14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…It is also comparable to the estimated clearance found in a recent study in critically ill children where they also found an effect of inflammation (to compare these values, the results of Vet et al were adapted to values for a 70 kg individual) . In our model, a patient with a healthy albumin level of 45 g l −1 would have a midazolam clearance of 15.3 l h −1 , which is also in line with the results of other studies in healthy volunteers and obese patients , although some studies in obese patients and patients who had undergone bariatric surgery have even higher clearance values . The estimated value for volume of distribution is also similar to that of the studies in critically ill patients and that of the most recent study in obese patients .…”
Section: Discussionsupporting
confidence: 90%
“…It is also comparable to the estimated clearance found in a recent study in critically ill children where they also found an effect of inflammation (to compare these values, the results of Vet et al were adapted to values for a 70 kg individual) . In our model, a patient with a healthy albumin level of 45 g l −1 would have a midazolam clearance of 15.3 l h −1 , which is also in line with the results of other studies in healthy volunteers and obese patients , although some studies in obese patients and patients who had undergone bariatric surgery have even higher clearance values . The estimated value for volume of distribution is also similar to that of the studies in critically ill patients and that of the most recent study in obese patients .…”
Section: Discussionsupporting
confidence: 90%
“…26,27 Additionally, CYP3A activity exhibits diurnal variation, with nevirapine clearance rates increasing during the day and reducing at night. 28,29 Differences between morning (AM) and evening (PM) nevirapine trough concentrations ( C min ) have been previously reported 30 and may relate to diurnal variation in the CYP3A -mediated effects on pharmacokinetics.…”
Section: Introductionmentioning
confidence: 89%
“…43 The effect of diurnal variations was investigated using step or cosine functions. 29 Besides weight and age, the other covariates tested were: study site, NRTI treatment backbone, sex, weight-for-age Z-score (WAZ), height-for-age Z-score (HAZ) and formulation. Pharmacogenetic effects were tested as individual SNPs (rs3745274, rs28399499, rs4803419, rs35599367, rs776746, rs3003596, rs2307424, rs2472677, rs2125739) and as metabolizer status determined by SNPs 516G > T and 983T > C [EM, genotype 516GG|983TT; intermediate metabolizer (IM), single variant allele (516GT|983TT or 516GG|983TC); slow metabolizer (SM), two variant alleles (516TT|983CC or 516GT|983TC); ultra-slow metabolizer (USM), 983CC irrespective of 516G > T genotype].…”
Section: Chapas-1mentioning
confidence: 99%
“…16 On the other hand, other studies have not found such a pattern. 17,18 In a study conducted in children hospitalized in intensive care units, and with the use of population pharmacokinetics, the light-dark cycle was found to have no impact on CYP3A activity. 19 The primary objective of this prospective study was to test the existence of a circadian rhythm in the hepatic CYP3A activity, and quantify its magnitude.…”
mentioning
confidence: 99%